Anisotropic optical polarization dependence on internal strain in AlGaN epilayer grown on AlxGa1−xN templates. (16th September 2016) - Long, Hanling; Wu, Feng; Zhang, Jun; Wang, Shuai; Chen, Jingwen; Zhao, Chong; Feng, Zhe Chuan; Xu, Jintong; Li, Xiangyang; Dai, Jiangnan; Chen, Changqing
Abstract: Anisotropic optical polarization of AlGaN has been one of the major challenges responsible for the poor efficiency of AlGaN-based ultraviolet light emitting diodes (UV LEDs). In this work, we experimentally investigated the effect of internal strain on the optical polarization of AlGaN epilayers which were pseudomorphically grown on Al x Ga1− x N templates with Al composition changing from 0.1 to 0.42. High-resolution x-ray diffraction and reciprocal space mapping were conducted to determine the crystal quality and strain status. Polarization-dependent photoluminescence (PL) measurement was performed to study the degree of polarization (DOP) of light emission from lateral facet of the AlGaN epilayer. The result showed that the DOP increased from −0.69 to −0.24 with the in-plane strain changing from tensile status (1.19%) to compressive status (−0.70%) and it exhibited a strong dependence of the DOP on the strain. These results demonstrated that the compressive in-plane strain could facilitate TE mode emission from AlGaN, which providing a potential way to enhance the surface light emission of AlGaN-based UV LEDs via strain management of the active region.